Pursuing Maritime Education in Digital Era: Students’ Voices - Pratiwi, Damar Isti; Prayogo, Darul; Runadi, Taruga (Jurnal Pendidikan Progresif, 2023)
Pursuing maritime education in digital era: students voices. Technology advancement shifts maritime education's focus from theoretical concepts to practical action. Therefore, this study investigated the perspectives of vocational students and the obstacles during undertaking degrees in maritime institution. It engaged 200 students from an Indonesian maritime college, which employed a mixed-method research design using closed and open-ended questionnaires. The results of quantitative data revealed students’ high acceptance in pursuing maritime education, which was affected by five factors: high-qualified education, friends, practical skill, economic motif, and job availability. The qualitative data showed challenges regarding financial problems, time management, adaptation, technological development, and foreign language problems. Some possible solutions considered scholarships, having peers, being selective in joining campus activities, and improving skills and knowledge. Hence, maritime institutions should improve their qualification in the digital era. Students have to be equipped with technology-practical-based skills to become professionals in the maritime sector. Keywords: education, maritime education, pursuing education, digital era.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202321